Intra-articular hydrogel formulation prolongs the in vivo stability of Toll-like receptor antagonistic peptides for rheumatoid arthritis treatment - Lee, Soyeon; Choi, Sangdun; Kim, Moon Suk (Journal of Controlled Release, 2024)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by systemic inflammation that primarily affects joint tissue and requires frequent medication. Recently, we developed cyclic phage-display-derived inhibitory peptides (CPs), which act as Toll-like Receptor 4 antagonists. These CPs exhibited therapeutic efficacy against joint diseases by alleviating inflammatory factors. Nonetheless, CP exhibits in vivo instability and a short half-life. Therefore, this study sought to improve the in vivo stability of CP, thereby reducing the frequency of CP administration through the development of an injectable hydrogel depot formulation. To improve in vivo stability, CP was chemically conjugated to hyaluronic acid (HA—CP) and subsequently mixed into a temperature-sensitive hydrogel [methoxy polyethylene glycol-b-poly(ε-caprolactone)-ran-poly(lactide) (PC)] as an injectable depot (PC+(HA—CP)). For comparison, CP was physically mixed with HA and PC (PC+(HA+CP)). Both PC+(HA—CP) and PC+(HA+CP) were found to rapidly form depots upon injection into the joint space. Cell viability assays confirmed the non-toxic nature of PC+(HA—CP) and PC+(HA+CP), whereas both formulations exhibited inhibition of inflammatory factors. Furthermore, PC+(HA—CP) retained CP for a longer duration compared to PC+(HA+CP) in the presence of hyaluronidase and within the RA joint space. Following intra-articular injection, both the PC+(HA—CP) and PC+(HA+CP) depots exhibited reductions in RA symptoms, cartilage regeneration, and suppression of pro-inflammatory cytokine levels. Specifically, by extending the in vivo retention of CP, PC+(HA—CP) demonstrated superior RA treatment efficacy compared to PC+(HA+CP). In conclusion, intra-articular injection of PC+(HA—CP) was validated as an effective strategy for treating RA, owing to its ability to prolong the in vivo retention of CP. This approach holds promise for improving RA management and patient outcomes.
Keywords: Autoimmune disease; In-vivo; Intra-articular injection; Joint space; Long lasting; Long-lasting release; Rheumatoid arthritis; Thermo-sensitive hydrogel; Thermosensitive hydrogel depot; Toll-like receptors; Animals; Antirheumatic Agents; Arthritis, Experimental; Arthritis, Rheumatoid; Drug Stability; Hyaluronic Acid; Hydrogels; Injections, Intra-Articular; Male; Mice; Peptides; Polyesters; Hyaluronic acid; Intra-articular injection; Long-lasting release; Rheumatoid arthritis; Thermosensitive hydrogel depot